Paleoparasitological study on the soil sediment samples from archaeological sites of ancient Silla Kingdom in Korean peninsula. (16th June 2016) - Kim, Myeung Ju; Seo, Min; Oh, Chang Seok; Chai, Jong-Yil; Lee, Jinju; Kim, Gab-jin; Ma, Won Young; Choi, Soon Jo; Reinhard, Karl; Araujo, Adauto; Shin, Dong Hoon
Abstract: Due to paleoparasitology's relatively late beginnings, the fundamental data necessary for any reasonably complete understanding of parasitic infection patterns in Korean history remains insufficient. Especially with respect to ancient samples dating to before the Joseon Dynasty (1392–1910 CE), few cases have been analyzed by parasitological techniques. In the present study, we therefore undertook a series of paleoparasitological examinations of archaeological samples from the ancient Silla Kingdom (57 BCE–935 CE). Specifically, in soil samples obtained from shell midden and mountain top fortress sites, we observed Ascaris lumbricoides, Trichuris trichiura, Dicrocoelid and Taenia sp. eggs. The results of our current investigation of strata and samples from the prosperous first-millennium era of the Silla Kingdom are encouraging for a comprehensive understanding of the parasitic infection patterns in the earlier days of Korean history that could not be obtained by any previous studies.